Psychological well-being of students as a precondition for their professional self-realization - Anna P. Shmakova, Albina Z. Minakhmetova, Natalia N. Radchenko, (Opción, 2019)
The purpose of our research is to identify the relationship between the psychological well-being of students and their professional self-realization. In our research, we used the Ryff Scale to measure the following six factors: autonomy, competence, personal growth, positive relations with others, and purpose in life, self-acceptance and the overall indicator. According to the results of the multidimensional questionnaire, 43% of the respondents are characterized by a harmonious level of self-development. In conclusion, the students with a high Autonomy factor may have difficulties in finding compromises and working in a team.